Training volume and training frequency changes associated with boston marathon race performance - DeJong Lempke, A. F.; Ackerman, K. E.; Stellingwerff, T.; Burke, L. M.; Baggish, A. L.; d`Hemecourt, P. A.; Dyer, S.; Troyanos, C.; Saville, G. H.; Adelzadeh, K.; Holtzman, B.; Hackney, A. C.; et al. (Sports Medicine, 2026)
Background: Physical training influences competitive marathon performance, including training volume and training frequency changes (TFCs) pre-race. Training intensity distribution (i.e., steady-state, quality sessions, interval training) and cross-training contribute to volume and TFCs that may influence performance. Objective: The aim of this study is to assess the relationships among training and TFCs preceding the 2022 Boston Marathon and race performance. Methods: Adult 2022 Boston Marathon registrants were contacted via email 1 month pre-race. Athletes reported demographics, training/racing experience, and training pre-race. TFCs were calculated by comparing two timeframes: 12-4 and 4-0 month pre-race training. Official race performance was obtained from chip timing data and demographics. Separate linear regressions were used to assess the effects of training and cross-training in 12-4 and 4-0 months pre-race and TFCs on performance, accounting for experience and demographics. Results: In total, 917 athletes were included (female: n = 495, 3:53 ± 0:37 h race times, 64.4 ± 24 km/week weekly distance; male: n = 422; 3:35 ± 0:39 h race times, 67.6 ± 26.2 km/week weekly distance). Higher running distance/week, running sessions/week (n), quality sessions/week ("hard sessions"; n), average distance in the 12-4 and 4-0 months pre-race (p = 0.050), and more cross-training (p < 0.001) in the 4-0 months pre-race were associated with faster times and performance. Runners with TFCs of decreased running sessions/week (p = 0.035) had faster times and better performance versus athletes who maintained/increased volume. Conclusion: Habitually higher training exposure 12-4 and 4-0 months, but relatively reduced training frequency 4-0 months pre-race, contributed to better marathon performance.